The Myth of The Tiger in The Minang Community: Flora and Fauna Conservation Efforts - Ninawati Syahrul; Sastri Sunarti; Atisah Atisah (International Journal of Science and Applied Science: Conference Series, 2022)
This study attempts to describe the Minang people's belief in tigers contained in tiger myths and legends. The story of the tiger will be described and analyzed by interpretive qualitative descriptive method. The theory used is the cultural interpretation approach by Geertz and myth analysis by Levy Strauss. The results of the study are in the form of a description of the intricacies of the Minang people's traditional belief in tigers. This research is also expected to support the conservation of flora and fauna, especially tigers. Stories of tigers and belief in tigers can be developed as material for enrichment of industry 4.0-based literacy. more accessible to the younger generation.